Oral feeding in Huntington''s disease: a guideline document for speech and language therapists. (February 2012) - Hamilton, Alison; Heemskerk, Anne-Wil; Loucas, Melissa; Twiston-Davies, Rita; Matheson, Kirsty Y; Simpson, Sheila A; Rae, Daniela
SUMMARY Speech and language therapy has an important role in the management of Huntington''s disease (HD). Swallowing difficulties affect most individuals with HD. Throughout the disease process these difficulties require management with timely and effective therapeutic intervention. Currently there are no European guidelines for the assessment and management of swallowing impairments in HD. The European Huntington''s Disease Network (EHDN) Standards of Care Speech and Language Therapy Working Group has brought together expert speech and language therapists from across Europe to produce guidelines to improve the management of swallowing disorders for individuals with Huntington''s disease. The guidelines were developed with the aim of promoting timely and appropriate assessment of the swallowing process and focused management throughout all stages of the disease. Literature was systematically searched in an attempt to ensure that the recommendations are based on sound evidence. Where evidence was lacking, specific guidance is based on expert consensus. The provision of care varies widely between countries in Europe and the implementation of those guidelines should improve the quality of care delivered to individuals with HD.